Governance Model for Blue Economy Policy Implementation Developing Marine MSMEs Based on Processed Fishery Products to Foster Self-Reliance Among the Coastal Community of Karangantu, Serang Regency - Ahmad Rifa’i (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The blue economy has become a strategic approach to promoting sustainable coastal development by optimizing marine resources while preserving environmental sustainability. However, the implementation of blue economy policies in Karangantu Coastal Area, Serang Regency, has not yet effectively strengthened the competitiveness and independence of marine micro, small, and medium enterprises (MSMEs) based on processed fishery products. This study aims to develop a governance model for implementing blue economy policies that supports the sustainable development of marine MSMEs and enhances the self-reliance of coastal communities. The research employed a qualitative case study approach using in-depth interviews, observation, documentation, and focus group discussions involving government agencies, MSME actors, fishermen, academics, and community organizations. Data were analyzed through data reduction, data display, and conclusion drawing with source triangulation to ensure validity. The findings indicate that effective governance depends on collaborative interaction among government institutions, business actors, communities, and academic institutions through integrated policies, capacity building, digital marketing, financial access, and innovation in processed fishery products. The proposed governance model strengthens institutional collaboration, resource utilization, and market competitiveness, thereby contributing to sustainable coastal economic development and improving the welfare and economic self-reliance of the Karangantu coastal community